Implementation of Question and Answer Method in Efforts to Improve the Quality of Fiqh Education Learning for Students at Nurul Ikhwan Betung Elementary School - Winda; Gusriani, Wira; Winarti; Wiwie; Sugiarti, Wiwi (MANDAILING GLOBAL EDUKASIA, 2025)
Fiqh education is one of the important components in Islamic religious learning at the elementary school level. However, various challenges in the learning process often arise, especially related to the lack of variation in the methods used. This article aims to explore the application of the question and answer method as an effort to improve the quality of fiqh learning for grade 6 students at MI Nurul Ikhwan Betung. This study uses a classroom action research (CAR) approach with two implementation cycles. Each cycle consists of planning, action, observation, and reflection stages, which aim to identify changes in student understanding and participation during learning. The results of the study indicate that the application of the question and answer method can increase active interaction between teachers and students, deepen students' understanding of fiqh material, and increase students' motivation and confidence in following lessons. This method has also proven effective in creating a more interesting and enjoyable learning atmosphere, so that students are more actively involved. Based on the results of this study, it is recommended that teachers use the question and answer method routinely in fiqh learning to improve the quality of education at MI Nurul Ikhwan Betung, and can be adapted in other schools with similar conditions.